Preparation of Poly (dl-Lactide-co-Glycolide) Nanoparticles Encapsulated with Periglaucine A and Betulinic Acid for In Vitro Anti-Acanthamoeba and Cytotoxicity Activities - Mahboob, Tooba; Nawaz, Muhammad; Tan, Tian Chye; Samudi, Chandramathi; Wiart, Christophe; Nissapatorn, Veeranoot (MDPI, 2018)
Poly (DL-lactide-co-glycolide) (PLGA) microspheres were synthesized as delivery system for the natural anti-parasitic compounds, Periglaucine A (PGA) and Betulinic acid (BA). Periglaucine A and Betulinic acid were encapsulated in PLGA nanoparticles by single emulsion method with an average particle size of approximately 100–500 nm. Periglaucine A and Betulinic acid encapsulation efficiency was observed to be 90% and 35% respectively. Anti-Acanthamoeba property of Periglaucine A and Betulinic acid remained intact after encapsulation. PGA-PLGA and BA-PLGA nanoparticles demonstrated inhibition in viability of Acanthamoeba triangularis trophozoites by 74.9%, 59.9%, 49.9% and 71.2%, 52.2%, 88% respectively at concentration of 100 µg/mL, 50 µg/mL and 25 µg/mL. Cytotoxicity of PGA-PLGA and BA-PLGA nanoparticles has been evaluated against lung epithelial cell line and showed dose dependent cytotoxicity value of IC50 2 µg/mL and 20 µg/mL respectively. Futher, increased viability was observed in lung epithelial cell line in higher doses of synthesized polymeric nanoparticles. Results indicate that poly (DL-lactide-co-glycolide) (PLGA) nanoparticles could be exploratory delivery systems for natural products to improve their therapeutic efficacy.